THE EFFECT OF PRODUCT KNOWLEGDE, ONLINE CUSTOMER REVIEW, ONLINE CUSTOMER RATING AND PRICES ON CONSUMER BUYING INTEREST IN MEDIATION OF TRUST IN THE MARKETPLACE SHOPEE (STUDY AT MWCNU SUKODADI) - Winda Listya Anggraini; Abid Muhtarom; Akhlis Priya Pambudy; Yuhronur Efendi; Deddi Nordiawan; Abdul Ghofur (Bajang Institute, 2022)
The era of increasingly sophisticated technology, it causes a shift in consumer behavior, especially in shopping. Online shopping has now become a habit. There are factors that consumers consider, namely safety or inappropriate goods. In this study there is a novelty, namely more variables that are examined and the object of research. This research is a quantitative study that has a sample of 165 respondents and the data analysis used is the SEM method with the Smart PLS version 3.0 tool. The test used is the outer model test, the structural model, mediation and hypotheses. The results show that The validity test has an outer load mg value > 0.7 and an AVE value > 05 then it is declared valid. The reliability test shows a composive reliability value and Cronbach's alpha > 07 then it is said to be reliable. said Partial Mediation Online customer review variable (X2) on buying interest (Y) mediated by trust (Z) said Non Mediation Online customer rating variable (3) on buying interest (Y) mediated trust (Z) said Non Mediation Price variable (X4) on buying interest (Y) mediated by trust (Z) is said to be Partial Mediation Based on the analysis of the test results The hypothesis can be concluded that the product knowledge variable (X1). Online customer review (X2), online customer rating (X3) and price (X4) on bell interest (Y) simultaneously have a positive and significant effect